A COMPARATIVE STUDY ON DISCOURSE ANALYSIS OF KOREAN MOVIE "THE HOUSEMAID" – FOCUSED ON FILMS IN 1960 AND 2010 – - KIM, Eunhye (International Journal of Korean Humanities and Social Sciences, 2020)
Korean legendary film director Kim Ki-Young’s 1960 work The Housemaid was remade in 2010 by director Im Sang-Soo. The study of the two films can be found as a comparative study of cinematic studies on sound analysis and genre analysis, and a sociological study on social images. However, few studies have looked with a discourse oriented approach. Discourse in the movie is not only a window for communication between characters, but also an important device with non-verbal elements, so it can be said to be discourse has a high importance as an analysis target. This study analyzes the film discourse according to Erving Goffman’s dramaturgical analysis to find out the differences between the characters. This study can be said is meaningful in that it has the characteristics of interdisciplinary research in linguistics and film studies through discourse analysis of two films with different periods.